Effectiveness of biomolecule-based bioactive surfaces, on os-seointegration of titanium dental implants: A systematic review and meta-analysis of in vivo studies - López-Valverde, Nansi; Aragoneses, Javier; López-Valverde, Antonio; Quispe-López, Norberto; Rodríguez, Cinthia; Aragoneses, Juan Manuel (Frontiers in Bioengineering and Biotechnology, 2022)
Titanium and alloy osseointegrated implants are used to replace missing teeth; however, some fail and are removed. Modifications of the implant surface with biologically active substances have been proposed. MEDLINE [via Pubmed], Embase and Web of Science were searched with the terms "titanium dental implants", "surface properties", "bioactive surface modifications", "biomolecules", "BMP", "antibacterial agent", "peptide", "collagen", "grown factor", "osseointegration", "bone apposition", "osteogenic", "osteogenesis", "new bone formation", "bone to implant contact", "bone regeneration" and "in vivo studies", until May 2022. A total of 10,697 references were iden-tified and 26 were included to analyze 1,109 implants, with follow-ups from 2 to 84 weeks. The ARRIVE guidelines and the SYRCLE tool were used to evaluate the methodology and scientific evidence. A meta-analysis was performed (RevMan 2020 software, Cochane Collaboration) with random effects that evaluated BIC at 4 weeks, with subgroups for the different coatings. The heterogeneity of the pooled studies was very high (95% CI, I2=99%). The subgroup of BMPs was the most favorable to coating. Surface modification of Ti implants by organic bioactive molecules seems to favor osseointegration in the early stages of healing, but long-term studies are necessary to corroborate the results of the experimental studies.